Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menggunakan Metode Weighted Product - Eka W Fridayanthie; Nanda Khoirurrizky; Tri Santoso (Paradigma, 2020)
Employees are one of the most important factors in a company, without it a company will not be able to run smoothly, but over time an employee needs encouragement in carrying out his duties. With the holding of the best employee selection on CV. Laatansa Agung Tangerang will re-ignite the enthusiasm of all employees but because the selection that has been done is chosen subjectively then the desired results are not appropriate. This is where the adoption of a decision support system can be used and one method that can be easily understood and used is a weighted product method which will calculate each alternative and raised with its weight the greater the value of an alternative, the greater the chance to be chosen. This application is in accordance with the problems experienced by CV. Laatansa Agung Tangerang where the results obtained will be objective because they are carried out based on the assessment that occurs in the field not based on a unilateral or subjective assessment and from here the results obtained will trigger employees of CV. Laatansa Agung Tangerang to competing to be the best employee